Implementación de un sistema contable en la Compañía Petrokasama S.A. de la ciudad de Santo Domingo periodo abril-junio 2013 - Delgado Bastidas, Robert Teodoro (2015)
This research is about the IMPLEMENTATION OF A SYSTEM ACCOUNTING IN THE COMPANY "PETROKASAMA" S.A. OF SANTO DOMINGO CITY APRIL-JUNE 2013 PERIOD, which allowed us to put into practice all the knowledge acquired in the process of learning in the classrooms of the University and as a result could know the accounting information according to the reality of the company In addition, provided the necessary guidelines so that the leaders of the entity can be monitored that accounting is carried out properly. In the development of this work the objectives were achieved, where the main objective is to contribute to the improvement of the recordable side with the implementation of an accounting system. This thesis was do it with data obtained from the company, starting with the inventory in order to initiate the accounting process and determine the assets of the company, later the plan was designed and then manual account using accounts that the Superintendency of Companies requested the presentation of financial statements the company, was the accounting entries settings and closure generated books accounting and thus finally to make the financial statements. At the end of the implementation, we can say that the necessary guidelines for the development of the accounting process by responsible persons were established